SOSIALISASI DIAGNOSIS LIDAH UNTUK DETEKSI GANGGUAN REPRODUKSI PADA TERAPIS HOLISTIK SOLO RAYA - Sri Kustiyati; Istiqomah Risa Wahyuningsih; Rita Riyanti Kusumadewi (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The socialization of tongue condition assessment in patients with reproductive disorders is a strategic effort to enhance holistic therapists’ understanding of non-invasive health detection methods. Limited practitioner knowledge about the correlation between tongue changes and reproductive health creates a gap between theory and practice. This program aimed to strengthen practitioners’ competence in identifying reproductive health indicators through tongue diagnosis. The implementation involved interactive lectures, discussions, practical demonstrations, and evaluations using pre-tests, post-tests, and satisfaction questionnaires. Fifteen holistic therapy practitioners from Solo Raya participated. Evaluation results showed a notable improvement in knowledge, with average scores increasing from 51.4 (pre-test) to 69.47 (post-test), reflecting a 36% improvement. Participant satisfaction was rated “good to excellent,” with an average score of 4.4 on a 5-point scale. These outcomes demonstrate that the training effectively enhanced practitioners’ understanding and diagnostic skills. Consequently, this activity contributes significantly to strengthening traditional medicine-based health services and provides a model for similar future initiatives aimed at integrating holistic approaches in reproductive health care.